Corrosion monitoring of post-tensioned strands at the Piedra del Aguila spillway - Burkart, Arturo L.; Duffó, Gustavo Sergio; Castro, P. (Hydropower & Dams, Aqua-Media International Ltd, 2014)
Fil: Burkart, Arturo L.. Comisión Nacional de Energía Atómica; Argentina